The Atlantic slave trade - Northrup, David (Problems in world history, 1994)
Economics, not racism, as the root of slavery / Eric Williams -- The simultaneous invention of slavery and racism / Winthrop D. Jordan -- Sugar and slavery from the Old to the New World / David Brion Davis -- From guesses to calculations / Philip D. Curtin -- Curtin's calculations refined but not refuted / Paul E. Lovejoy -- A skeptical view of how much can be known / David Henige -- A skeptical view of Curtin's and Lovejoy's calculations / Joseph E. Inikori & Stanley L. Engerman -- An alliance to raid for slaves, 1568 / John Hawkins -- Trading on the slave coast, 1700 / Willem Bosman -- Kidnapped, enslaved, and sold away, c. 1756 / Olaudah Equiano -- A reformed slave trader's regrets, c. 1745-1754 / John Newton -- Kidnapping and retaliation, 1767-1768 / Richard Story -- Views of the king of Asante, 1820 / Osei Bonsu -- Views of a king at Old Calabar, 1850 / Eyo Honesty -- The middle passage / Malcolm Cowley & Daniel P. Mannix -- Profits and the causes of mortality / Herbert S. Klein -- Deaths before the middle passage / Joseph C. Miller -- The unequal partnership between Africans and Europeans / Walter Rodney -- Social and demographic transformations / Patrick Manning -- The economics of African participation in the slave trade / David Eltis -- The British antislavery squadron in 1822 / E. Gregory & Edward Fitzgerald -- Capitalism and abolitionism / Eric Williams -- The idea of progress / Howard Temperley -- Slave revolts and the end of slavery / Michael Craton